Spinel magnesium ferrite (MgFe2O4): a glycine-assisted colloidal combustion and its potentiality in gas-sensing application - Nadargi, Digambar; Umar, Ahmad; Nadargi, Jyoti; Patil, Jayvant; Mulla, Imtiaz; Akbar, Sheikh; Suryavanshi, Sharad (Chemosensors, 2022)
Herein, we describe the facile synthesis of spinel MgFe2O4 ferrite and its potential use as a gas sensor using a straightforward and reliable sol-gel approach, i.e., the glycine-assisted auto-combustion route. The novelty in obtaining the sensing material via the auto-combustion route is its inherent simplicity and capability to produce the material at an industry scale. The said cost-effective process makes use of simple metal salts (Mg and Fe-nitrates) and glycine in an aqueous solution, which leads to the formation of spinel MgFe2O4 ferrite. A single-phase crystallinity with crystallite sizes ranging between 36 and 41 nm was observed for the synthesized materials using the X-ray diffraction (XRD) technique. The porous morphologies of the synthesized materials caused by auto-ignition during the combustion process were validated by the microscopic investigations. The EDS analysis confirmed the constituted elements such as Mg, Fe, and O, without any impurity peaks. The gas-sensing ability of the synthesized ferrites was examined to detect various reducing gases such as LPG, ethanol, acetone, and ammonia. The ferrite showed the highest response (>80%) toward LPG with the response and recovery times of 15 s and 23 s, respectively. Though the sensor responded low toward ammonia (similar to 30%), its response and recovery times were very quick, i.e., 7 s and 9 s, respectively. The present investigation revealed that the synthesized ferrite materials are good candidates for fabricating high-performance sensors for reducing gases in real-world applications.
Keywords: Gas sensors; glycine combustion; MgFe2O4; reducing gases

Sponge microflowers of NiCo2O4: a versatile material for high performance supercapacitor - Ghadage, Ambar; Kodam, Pavan; Nadargi, Digambar; Shinde, K. P.; Mulla, Imtiaz; Park, J. S.; Suryavanshi, Sharad (Journal of Porous Materials, 2022)
We report the development of well optimised NiCo2O4 microflowers for high performance supercapacitor application. The efforts were made to optimise the electrode material by tuning the synthetic as well as electrolyte concentration parameters such as (i) hydrothermal reaction temperature, (ii) hydrothermal reaction time, (iii) sintering temperature, and (iv) electrolyte concentration. The physico-chemical and supercapacitive properties were analysed using TGA, XRD, SEM/TEM/HRTEM, XPS, BET, and electrochemical measurements. The well optimised electrode material was obtained at 150 degrees C hydrothermal reaction temperature, 12 h of hydrothermal reaction time, 300 degrees C sintering temperature, and 3 M KOH electrolyte concentration. The optimised sample displayed high specific -capacitance (1478 F/g), -energy density (16.5 Wh/kg), and -power density (248 W/kg). The specific capacitance can be retained to 97.61% after 1000 cycles. The developed NiCo2O4 microflower structures are well optimised and offer great promise for future industrial applications.
Keywords: hydrothermal; Microflowers; Nickel cobaltite; supercapacitor

Pd loaded bismuth ferrite: a versatile perovskite for dual applications as acetone gas sensor and photocatalytic dye degradation of malachite green - Ghadage, Pandurang; Kodam, Pavan; Nadargi, Digambar; Patil, Suraj; Tamboli, Mohaseen; Bhandari, Nagesh; Mulla, Imtiaz; Park, Chinho; Suryavanshi, Sharad (Ceramics International, 2023)
Herein we report the palladium loaded bismuth ferrite for its bidirectional application as acetone gas sensor and photocatalytic dye degradation of malachite green. The motivation for loading Pd on bismuth ferrite (BFO) is due to its fascinating catalytic redox reactions causing faster adsorption and desorption of the oxygen molecules over the metal oxide. The planned perovskites were developed via surfactant assisted sol-gel auto-combustion route, and characterized their physico-chemical properties using XRD, SEM, TEM, HRTEM, EDAX, XPS and BET. The developed BFO showed the best selectivity towards acetone, whose response was 69% at 300 degrees C operating temperature for 500 ppm gas concentration. By tuning the surface area and catalytic behavior using CTAB and Pd loading, respectively, the enhancement in the gas response properties of BFO was achieved to 95% with the response and recovery time of 75 s and 104 s. The 1 wt% Pd loaded BFO showed the highest response (95%) in comparison to rest of the Pd loadings (0.5, 1.5 and 2.0 wt%). Moreover, the sunlight driven photocatalytic dye degradation of malachite green is carried out at 1 h exposure time. Here as well, 1 wt% Pd loaded BFO exhibited the maximum dye degradation efficiency of 51%. The results of this study demonstrate the developed perovskites have a significant potential for the use in dual applications such as acetone gas sensor and MG photocatalysis.
Keywords: Acetone sensor; Bismuth ferrite; Palladium loading; Photo dye -degradation

Bismuth ferrite based acetone gas sensor: evaluation of graphene oxide loading - Ghadage, Pandurang; Shinde, K. P.; Nadargi, Digambar; Nadargi, Jyoti; Shaikh, Hamid; Alam, Mohammad Asif; Mulla, Imtiaz; Tamboli, Mohaseen S.; Park, J. S.; Suryavanshi, Sharad (RSC Advances, 2024)
We report a BiFeO3/graphene oxide (BFO/GO) perovskite, synthesized using a CTAB-functionalized glycine combustion route, as a potential material for acetone gas sensing applications. The physicochemical properties of the developed perovskite were analysed using XRD, FE-SEM, TEM, HRTEM, EDAX and XPS. The gas sensing performance was analysed for various test gases, including ethanol, acetone, propanol, ammonia, nitric acid, hydrogen sulphide and trimethylamine at a concentration of 500 ppm. Among the test gases, the developed BFO showed the best selectivity towards acetone, with a response of 61% at an operating temperature of 250 degrees C. All the GO-loaded BFO samples showed an improved gas sensing performance compared with pristine BFO in terms of sensitivity, the response/recovery times, the transient response curves and the stability. The 1 wt% GO-loaded BiFeO3 sensor showed the highest sensitivity of 89% towards acetone (500 ppm) at an operating temperature of 250 degrees C. These results show that the developed perovskites have significant potential for use in acetone gas sensing applications. CTAB-functionalized glycine combustion yields BiFeO3/graphene oxide (BFO/GO) perovskite for acetone gas detection.